The Kadtabanga Foundation for Peace and Development Advocates Incorporated (KFPDAI): A Peace-Building Exemplar - Usop, Annierah M (EDUCARE, 2013)
ABSTRACT: The purpose of this study is to find out whether or not the programs and activities employed by the Kadtabanga Foundation for Peace and Development Incorporated (KFPDAI) is a peace-building exemplar. The study may provide valuable information to the Philippine Government and the United Nations Development Program on the specific programs and projects that have been implemented in the conflict affected communities so as to realize one of the provisions of the 1996 GRP-MNLF (Government of the Republic of Philippines â Moro National Liberation Front) Final Peace Agreement which is on the âextensive peace and development efforts in Southern Philippinesâ. The study may make them aware that the processes and means of Non-Governmental Organizations are rigid and they could assure success. Furthermore, there is still a dearth of materials regarding interventions for the purpose of rebuilding communities affected by armed conflict, especially in the Philippines. This study is hoped to contribute something. Whereas based on the major findings, the researcher concluded that the KFPDAI is a peace-building exemplar. However, there are still challenges, but challenge does not mean they have failed to be a model. When the challenges are known, that is where enhancement begins. KEY WORDS: Kadtabanga foundation, development, Philippine government, Bangsamoro, peace-building, and organizational exemplar.About the Author: Annierah M. Usop is a Ph.D. Student at the School of Social Sciences USM (Science University of Malaysia), USM Campus, 1800 Minden, Pulau Pinang, Malaysia. She can be contacted via her e-mail address at: asiyyahusop@yahoo.comHow to cite this article? Usop, Annierah M. (2013). âThe Kadtabanga Foundation for Peace and Development Advocates Incorporated (KFPDAI): A Peace-Building Exemplarâ in EDUCARE: International Journal for Educational Studies, Vol.5(2) February, pp.223-240. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 7, 2012); Revised (January 15, 2013); and Published (February 17, 2013).Â Â